Oviposition Deterrence and Egg Hatch Inhibition of Fruit Fly, Bactrocera tau (Walker) by Some Plant Products, Bio-pesticides and Clay - Thakur, Priyanka; Gupta, Divender (International Journal of Bio-resource and Stress Management, 2016)
In laboratory studies, different concentrations of azadirachtin (0.005%, 0.01% and 0.015%), neem oil (1%, 2% and 3%, respectively), pongamia oil (1%, 2% and 3%), Beauveria bassiana (Daman 1% WP 0.1%, 0.5% and 1%) and clay (6%, 8% and 10%) were evaluated for oviposition deterrence against fruit fly, Bactrocera tau on cucumber. Azadirachtin (0.015%) followed by neem oil (3%), Daman (1%) and clay (10%) proved effective with 89.09%, 80.24%, 83.40% and 89.29% oviposition deterrence over control, respectively. Beauveria bassiana (Daman 1% WP), a formulation based on Beauveria bassiana, when used @ 0.1, 0.5 and 1.0% concentrations resulted in 6.65, 6.39 and 5.02 eggs female-1 with an oviposition deterrence values of 77.46, 78.23 and 83.40% over control, respectively. Cucumber slices when dipped in pongamia oil (1%, 2% and 3%) caused degradation in the tissues due to which further studies could not be carried out under laboratory conditions. Egg hatchability in different treatments was also worked out. The egg hatch also decreased with the increase in concentrations of test materials. Minimum egg hatch (32.75%) was recorded in azadirachtin (0.015%) treatment. The egg hatch in other treatments viz. Daman, neem oil and clay was 39.79, 59.47 and 61.00%, respectively at 1, 3 and 10% concentrations. Azadirachtin (0.015%), neem oil (3%), Daman (1%) and clay (10%) resulted in 32.75%, 59.47%, 39.79% and 61.00% egg hatch accounting for 2.5, 1.5, 2.2 and 1.5 times decrease over control.